Das Drama der Weimarer Republik und der Aufstieg des National sozialismus: der Feind Steht Rechts - Sowerby, Gudrun (1988)
This thesis examines plays written in the period from 1923 to 1933, whose subject matter is the rise of right wing radical forces and ultimately the rise of Hitler. Twelve plays, including those of well known authors such as Ernst Toller, Georg Kaiser, and Oedön von Horväth, as well as plays of minor authors, were chosen solely on the grounds of their antifascist stance. An attempt was made to interpret and analyse their contribution to the theory of fascism. The economic, socio-political and psychological issues raised in each individual play are examined in close reference to the historical events of the Weimar Republic and related to current thoughts on fascism.